The Incoherent Fluctuation of Folate Pools and Differential Regulation of Folate Enzymes Prioritize Nucleotide Supply in the Zebrafish Model Displaying Folate Deficiency-Induced Microphthalmia and Visual Defects - Hsiao, Tsun-Hsien; Lee, Gang-Hui; Chang, Yi-Sheng; Chen, Bing-Hung; Fu, Tzu-Fun (Frontiers in Cell and Developmental Biology, 2021)
Objective Congenital eye diseases are multi-factorial and usually cannot be cured. Therefore, proper preventive strategy and understanding the pathomechanism underlying these diseases become important. Deficiency in folate, a water-soluble vitamin B, has been associated with microphthalmia, a congenital eye disease characterized by abnormally small and malformed eyes. However, the causal-link and the underlying mechanism between folate and microphthalmia remain incompletely understood. Methods We examined the eye size, optomotor response, intracellular folate distribution, and the expression of folate-requiring enzymes in zebrafish larvae displaying folate deficiency (FD) and ocular defects. Results FD caused microphthalmia and impeded visual ability in zebrafish larvae, which were rescued by folate and dNTP supplementation. Cell cycle analysis revealed cell accumulation at S-phase and sub-G1 phase. Decreased cell proliferation and increased apoptosis were found in FD larvae during embryogenesis in a developmental timing-specific manner. Lowered methylenetetrahydrofolate reductase (mthfr) expression and up-regulated methylenetetrahydrofolate dehydrogenase (NADP+-dependent)-1-like (mthfd1L) expression were found in FD larvae. Knocking-down mthfd1L expression worsened FD-induced ocular anomalies; whereas increasing mthfd1L expression provided a protective effect. 5-CH3-THF is the most sensitive folate pool, whose levels were the most significantly reduced in response to FD; whereas 10-CHO-THF levels were less affected. 5-CHO-THF is the most effective folate adduct for rescuing FD-induced microphthalmia and defective visual ability. Conclusion FD impeded nucleotides formation, impaired cell proliferation and differentiation, caused apoptosis and interfered active vitamin A production, contributing to ocular defects. The developmental timing-specific and incoherent fluctuation among folate adducts and increased expression of mthfd1L in response to FD reflect the context-dependent regulation of folate-mediated one-carbon metabolism, endowing the larvae to prioritize the essential biochemical pathways for supporting the continuous growth in response to folate depletion.